Combined effects of lithium and borate ions on the hydration of calcium sulfoaluminate cement. (July 2017) - Cau Dit Coumes, Céline; Dhoury, Mélanie; Champenois, Jean-Baptiste; Mercier, Cyrille; Damidot, Denis
Abstract: This work investigates the combined influence of borate and lithium ions on the hydration of two calcium sulfoaluminate (CSA) cements containing 0 or 10 wt% gypsum. On the one hand, borates are known to retard CSA cement hydration due to the rapid precipitation of ulexite. On the other hand, lithium ions accelerate CSA cement hydration thanks to the fast precipitation of Li-containing aluminum hydroxide. When borates and lithium are present simultaneously, these two mechanisms are superimposed. With a gypsum-free cement, a third process is additionally observed: lithium promotes the initial precipitation of a borated AFm phase which is later converted into a borated AFt phase when hydration accelerates. Lithium salts can counteract the retardation by sodium borate. However, their influence is limited once a sufficient amount of Li-containing Al(OH)3 seeds is formed. For the CSA cements under investigation, the threshold lithium concentration is close to 0.03 mmol/g of cement and similar with or without borate.